Pregnancy outcomes of a joint obstetric and rheumatology clinic in a tertiary centre: a 2-year retrospective study of 98 pregnancies. Issue 1 (28th March 2022) - Hum, Ryan Malcolm; David, Trixy; Lau, Yen June; Iftikhar, Hajira; Thornber, Sue; Simcox, Louise; Bruce, Ian; Tower, Clare; Ho, Pauline
Abstract: Objectives: The purpose of this study was to describe the maternal and fetal outcomes in patients with inflammatory rheumatic diseases attending a joint rheumatology and obstetric clinic in the UK. Methods: Electronic records of 98 patients attending the joint rheumatology and obstetric clinic between January 2018 and January 2020 were analysed. Data on patient demographics, characteristics (including age, ethnicity, diagnosis, and medications taken during pregnancy), pregnancy outcomes (miscarriage, stillbirth or live birth), maternal complications [infection, post-partum haemorrhage (PPH) or pre-eclampsia] and fetal complications (sepsis, congenital heart block, prematurity and low birth weight) were tabulated. Subgroups of patients based on maternal diagnosis, medications and Ro/La antibody status were described in a similar manner. Results: The cohort was found to be predominantly Caucasian women >30 years of age, diagnosed with a CTD. Of 98 pregnancies, 97% ( n = 95) resulted in a live birth, with only 2% resulting in miscarriage ( n = 2) and 1% in stillbirth ( n = 1). The median duration of gestation was 38 (interquartile range 37–39) weeks, and the majority of patients had a normal vaginal delivery (35%, n = 34), whereas 30% had emergency Caesarean sections ( n = 29). The median birth weight was 3120 (interquartile range 2690–3410) g. The most common maternal complications were PPH (56%, n = 54) and infection (22%, n = 21). The most common fetal complications were prematurity (23%, n = 22) and low birth weight (17%, n = 16). Conclusion: We report favourable outcomes from this service model, including a high live birth rate, a low miscarriage rate and a high median birth weight. With limited reported data of pregnancy outcomes from joint obstetric/rheumatology clinics, this service model might be beneficial in other centres.